2009
DOI: 10.1177/1076029609344981
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Pathway Inhibitor and P-Selectin as Markers of Sepsis-Induced Non-overt Disseminated Intravascular Coagulopathy

Abstract: Inflammation and coagulation occur concomitantly in sepsis. Thrombin activates platelet that leads to P-selectin translocation, which upregulate tissue factor (TF) generation. Tissue factor pathway inhibitor (TFPI) is an anticoagulant that modulates coagulation induced by TF. The term non-overt disseminated intravascular coagulation (DIC) refers to a state of affairs prevalent before the occurrence of overt DIC. It was suggested that an initiation of treatment in non-overt DIC has better outcome than overt DIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 53 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…[13] The results of our study indicated that CD62P is not only involved in inflammatory response by its relationship with hs-CRP and TNF-α, but also involved in platelet activation and subsequent widespread microthrombosis in microvessels via its relationship with D-dimer, AT-III activity, PT and APTT and that CD62P is an important initiating factor for infl ammatory response and coagulation/fibrinolysis dysfunction in sepsis. Mosad et al [14] found in 176 sepsis patients complicated with DIC, CD62P level was positively correlated with the level of DIC, fi brinogen consumption, D-dimer, and markers of thrombin activation. CD62P can not only initiate the inflammatory cascade but also trigger the coagulation cascade.…”
Section: Discussionmentioning
confidence: 98%
“…[13] The results of our study indicated that CD62P is not only involved in inflammatory response by its relationship with hs-CRP and TNF-α, but also involved in platelet activation and subsequent widespread microthrombosis in microvessels via its relationship with D-dimer, AT-III activity, PT and APTT and that CD62P is an important initiating factor for infl ammatory response and coagulation/fibrinolysis dysfunction in sepsis. Mosad et al [14] found in 176 sepsis patients complicated with DIC, CD62P level was positively correlated with the level of DIC, fi brinogen consumption, D-dimer, and markers of thrombin activation. CD62P can not only initiate the inflammatory cascade but also trigger the coagulation cascade.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, no association was searched between high levels of the biomarker and pneumonia. Several other clinical studies focusing on platelets as potential biomarkers for sepsis diagnosis and prognostication have been carried out but almost all concerned patients with sepsis as an inclusion criterion [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…First, platelet p-selectin expression results in increased monocyte TF expression and platelet adhesion to leukocytes and endothelium. [31, 32] Once adhered to leukocytes and endothelium, platelets serve as a surface for thrombin generation and cellular signaling of other coagulation factors. [8]…”
Section: Pathogenesis Of Thrombus Formation In Sepsismentioning
confidence: 99%